Graphic designer/illustrator / Syahrulfikri Salleh - Salleh, Syahrulfikri (Faculty of Art and Design, 2021)
Syahrulfikri Salleh (Ajin) is a graphic designer/illustrator from Malaysia based in Phnom Penh, Cambodia. He has been involved in the creative industry since 2000 and has exhibited his work in numerous local and international venues. In 2013, he quit his job as a lecturer of typography & graphic design to pursue his dream of traveling the world and making art by learning, sharing, and teaching. After two years of traveling by land from Kuala Lumpur to Spain, he accepted a job offer as Head of Art at an award-winning advertising agency in Phnom Penh. In 2015, he co-founded NOWHERE Art Studio, an independent artist-run space to learn, collaborate and inspire in Phnom Penh, Cambodia. Since then, he has curated exhibitions, residencies, talks, film screenings, art markets, art workshops, and social art projects. In 2018, he participated in Festival Tokyo, Japan representing the Phnom Penh art scene.